PENEGAKAN HUKUM TERHADAP SEDIAAN FARMASI YANG TIDAK MEMILIKI IZIN EDAR - Amanda, Jelli Putra; Yetti; Dewi, Sandra (Collegium Studiosum Journal, 2024)
Article 143 of Law Number 17 of 2023 on Health stipulates that: (1) Any individual who produces and/or distributes pharmaceutical preparations, medical devices, and household health supplies (PKRT) must obtain business permits from the Central or Regional Government in accordance with their authority, based on norms, standards, procedures, and criteria as stipulated by applicable laws and regulations. (2) Any individual who produces and/or distributes pharmaceutical preparations, medical devices, and PKRT that have obtained business permits but are proven to not meet safety, efficacy, and quality requirements shall be subject to administrative sanctions in accordance with laws and regulations in the field of business licensing. (3) Business permits as referred to in paragraph (1) do not apply to traditional herbal medicine (jamu) sellers, herbal medicine makers, and facilities for the production of specially used drugs. (4) Business licensing related to pharmaceutical preparations, medical devices, and PKRT as referred to in paragraphs (1) and (2) shall be carried out in accordance with applicable laws and regulations. The research method used is sociological legal research. Based on the research results in Pekanbaru, it was found that the regulation has not been implemented as expected. This is evident from the widespread presence of pharmaceutical products, including cosmetics and drugs, that do not have the required permits in the city. In the context of law enforcement against unlicensed pharmaceutical preparations, although the law provides a clear legal framework to regulate and supervise the circulation of drugs and cosmetics, significant challenges remain in effective monitoring and enforcement on the ground. Many drugs and cosmetics are circulated without distribution permits, posing potential risks to public health. Legal action against perpetrators who market illegal drugs or cosmetics must be carried out firmly and consistently, with appropriate penalties to create a deterrent effect and prevent the circulation of harmful illegal goods.